RANCANG BANGUN WEBSITE SEKOLAH DENGAN MENGGUNAKAN FRAMEWORK BOOSTRAP (STUDI KASUS MAN 11 JAKARTA SELATAN) - Teddy Erlan Inzaki; Indra Cahya Firdaus (CV. Multi Kreasi Media, 2023)
The role of information technology really helps various jobs become lighter. With the support of technology, any information needed will be easily obtained and conveyed. Various companies and agencies are required to use information technology as a measure of the quality of the company or agency. Educational institutions need an information technology for school data processing activities and present information quickly and accurately, so that in improving the quality of the school itself an information technology is needed to support information systems that can manage various information as needed. The data collection method used is the Library Study Method, which is a technique for finding data related to research sourced from books and documents in the form of journals, theses and related data needed to support system development. Question and answer forum that can be utilized by teachers and students who are still active or have student status at MAN 11 South Jakarta to continue to gain knowledge by exchanging ideas through a question and answer forum that has been developed and ready to be used. Student data and data for education staff or teaching staff have been presented dynamically using data from the MySQL database so that it will be easier when there are changes or additions to teaching staff data. Journals that were not previously available on the MAN 11 South Jakarta website have been added to the library menu, combined with the MAN 11 South Jakarta library books and included in the Journal Category.